2022
DOI: 10.1093/nar/gkac763
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput identification of RNA localization elements in neuronal cells

Abstract: Hundreds of RNAs are enriched in the projections of neuronal cells. For the vast majority of them, though, the sequence elements that regulate their localization are unknown. To identify RNA elements capable of directing transcripts to neurites, we deployed a massively parallel reporter assay that tested the localization regulatory ability of thousands of sequence fragments drawn from endogenous mouse 3′ UTRs. We identified peaks of regulatory activity within several 3′ UTRs and found that sequences derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…Even more overlap was observed between our subcellular proteome and two independent synapse transcriptomes ( Fig 2D ) [36, 37]. This intersection suggests that there may be a cohort of conserved genes required for maintenance of distal, subcellular structures [38, 39]. Furthermore, the non-overlapping genes may provide insights into RGC specific components and functions.…”
Section: Resultsmentioning
confidence: 96%
“…Even more overlap was observed between our subcellular proteome and two independent synapse transcriptomes ( Fig 2D ) [36, 37]. This intersection suggests that there may be a cohort of conserved genes required for maintenance of distal, subcellular structures [38, 39]. Furthermore, the non-overlapping genes may provide insights into RGC specific components and functions.…”
Section: Resultsmentioning
confidence: 96%
“…It has been previously shown that GA-rich motifs mediate targeting of Rab13 mRNA targeting to the actin rich cellular protrusions 37, 38 . Similarly, GA-rich motifs in Net1 mRNA were shown to mediate Net1 targeting to neurites 39 . Our RNAseq analysis of purified MBs showed Rab13 and Net1 mRNAs are also enriched in the MB, suggesting that the GA-rich motifs may also mediate CHMP4B mRNA targeting to the MBs.…”
Section: Discussionmentioning
confidence: 94%
“…It has been previously shown that GA-rich motifs mediate targeting of Rab13 mRNA targeting to the actin rich cellular protrusions 37,38 . Similarly, GA-rich motifs in Net1 mRNA were shown to mediate Net1 targeting to neurites 39 . Our RNAseq analysis of puri ed MBs showed Rab13 and Net1 mRNAs are also enriched in the MB, suggesting that the GA-rich motifs may also mediate CHMP4B mRNA targeting to the MBs.…”
Section: Discussionmentioning
confidence: 94%